2018
DOI: 10.1111/nep.13191
|View full text |Cite
|
Sign up to set email alerts
|

Green dialysis survey: Establishing a baseline for environmental sustainability across dialysis facilities in Victoria, Australia

Abstract: This survey provides a baseline for practices that potentially impact the environmental sustainability of dialysis units in Victoria, Australia. It also identifies achievable targets for attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…Shifting from the concept of eco-dialysis to the concept of green nephrology is not only semantic: green nephrology involves re-thinking all daily activities. Furthermore, it involves rethinking dialysis machines with a cradle-tocradle philosophy, building planet-friendly facilities and choosing renewable energies [16][17][18][19][20][21].…”
Section: Dialysis In the Global Contextmentioning
confidence: 99%
“…Shifting from the concept of eco-dialysis to the concept of green nephrology is not only semantic: green nephrology involves re-thinking all daily activities. Furthermore, it involves rethinking dialysis machines with a cradle-tocradle philosophy, building planet-friendly facilities and choosing renewable energies [16][17][18][19][20][21].…”
Section: Dialysis In the Global Contextmentioning
confidence: 99%
“…A recent survey of dialysis services in the Australian state of Victoria--a state where environmental issues seem better known than in most-confirmed little real appreciation of the environmental impact of dialysis. 19 Carbon footprint studies in nephrology are scarce. Only two studies from the United Kingdom 20,21 and one study from Australia 22 have attempted to calculate the carbon cost of HD, while only one study from China has documented the carbon footprint of PD.…”
Section: Dialysis and The Environment: Seeking A More Sustainable Futurementioning
confidence: 99%
“…Even an appreciation of the issues––in trained dialysis staff––appears rudimentary. A recent survey of dialysis services in the Australian state of Victoria––a state where environmental issues seem better known than in most––confirmed little real appreciation of the environmental impact of dialysis …”
Section: Introductionmentioning
confidence: 99%
“…In Australia, a recent survey of 71 public dialysis facilities in the state of Victoria showed that only 10% of the units used renewable sources of energy, solar in these cases, and 25% recycled reverse osmosis reject water for use elsewhere, such as to water gardens or flush toilets. 20 Although these countries are likely much 'greener' than other countries for which we do not have this baseline data yet, there is still much to be improved.…”
Section: Introductionmentioning
confidence: 97%